European Safety Analysis of mRNA and Viral Vector COVID-19 Vaccines on Glucose Metabolism Events - Gabriella di Mauro; Annamaria Mascolo; Miriam Longo; Maria Ida Maiorino; Lorenzo Scappaticcio; Giuseppe Bellastella; Katherine Esposito; Annalisa Capuano (MDPI AG, 2022)
Few data have been published on the effects of impaired glucose metabolism induced by COVID-19 vaccines. We decided to perform a study to describe Individual Case Safety Reports (ICSRs) of impaired glucose metabolism events reported in the European database (Eudravigilance, EV). ICSRs were retrieved from the online website of Eudravigilance. The reporting odds ratios (ROR) were computed to assess the reporting frequency for COVID-19 mRNA vaccines compared to COVID-19 viral vector-based vaccines. A total of 3917 ICSRs with a COVID-19 vaccine suspected were retrieved, with a total of 4275 impaired glucose metabolism events. Overall, the most reported events were related to "high glucose levels" (2012; 47.06%). The mRNA vaccines were associated with an increased reporting frequency of "type 1 diabetes mellitus" (ROR 1.86; 95% CI 1.33-2.60), "type 2 diabetes mellitus" (ROR 1.58; 95% CI 1.03-2.42), "high glucose levels" (ROR 1.16; 95% CI 1.06-1.27), "diabetes mellitus inadequate control" (ROR 1.63; 95% CI 1.25-2.11), and "hypoglycemia" (ROR 1.62; 95% CI 1.41-1.86) compared to viral vector-based vaccines. mRNA COVID-19 vaccines were associated with an increased reporting frequency of alterations of glucose homeostasis compared to viral-vector COVID-19 vaccines. Clinicians should be aware of these events to better manage glycemic perturbations. Larger nationwide studies are warranted to verify these findings.